Effect of progestin on thyroid function in female Wistar rats - Xie, Honglei; Qian, Tingting; Liu, Lanchun; Sun, Rong; Che, Wenjing; Zhao, Meng; Hou, Xin; Pan, Haowen; Su, Yue; Li, Jia; Dong, Xiaoqiu; Liu, Peng (Frontiers in Endocrinology, 2024)
To characterize the influence of female-specific hormones on women's thyroid function, the study investigated the influence of extra progestin from oral contraceptives on inducing thyroid dysfunction.Sixty female Wistar rats were divided into six groups based on levonorgestrel or desogestrel administration as the main active agents: control, low (0.0039 mg*20-fold), medium (0.0039 mg*100-fold), high (0.0318 mg*100-fold) levonorgestrel (pure product); and low (0.0083 mg*20fold) and high (0.0083 mg*100-fold) desogestrel (pure product). Progestin was administered by gavage every 4 days for 1 month. Statistical analysis was performed using one-way analysis of variance and the Kruskal-Wallis test. Following levonorgestrel gavage, serum free T4 and thyroidstimulating hormone levels were significantly lower in the experimental group than that in the control group (p=0.013 and 0.043). After desogestrel gavage, the serum free T4 and free T3 levels were lower in the experimental group than that in the control group (p=0.019 and 0.030). Thyroid hormone antibody concentrations were lower in rats administered levonorgestrel and desogestrel than that in control rats. Moreover, exposure to progestin upregulated the expression of the thyroid-stimulating hormone receptor and sodium iodide symporter in thyroid. Progestin stimulation enhanced the proliferation of follicular epithelial cells in rat thyroid tissues. Progestin exposure could cause thyroid dysfunction by upregulating the transcription of thyroid-stimulating hormone receptor and sodium iodide symporter in thyroid, thus inducing pathomorphological changes in rats' thyroid.